2015
DOI: 10.1074/jbc.m115.647487
|View full text |Cite
|
Sign up to set email alerts
|

Oxidatively Generated Guanine(C8)-Thymine(N3) Intrastrand Cross-links in Double-stranded DNA Are Repaired by Base Excision Repair Pathways

Abstract: Background: Base excision repair (BER) is the major pathway for repair of single oxidized nucleobases. Results: Bifunctional DNA glycosylases and AP endonucleases are able to remove cross-linked guanine in guanine(C8)-thymine(N3) intrastrand cross-links. Conclusion: BER pathways can repair the intrastrand cross-links. Significance: Oxidatively generated intrastrand cross-linked DNA lesions can be repaired in HeLa cell extracts not only by nucleotide excision repair, but also by multiple BER pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Such a 5Ј-fragment is not evident in our cell extract experiments ( Fig. 2A) because its mobility would be even slower than that of a fragment with a 3Ј-OH group (70).…”
Section: Ber and Ner Activities Are Observable In The Same Humanmentioning
confidence: 77%
“…Such a 5Ј-fragment is not evident in our cell extract experiments ( Fig. 2A) because its mobility would be even slower than that of a fragment with a 3Ј-OH group (70).…”
Section: Ber and Ner Activities Are Observable In The Same Humanmentioning
confidence: 77%
“…258 In vitro studies performed in HeLa cell extracts have demonstrated that the d(G[8- N 3]T) lesions could be potential substrates of both NER and BER pathways. 259,260 Another recent primer extension experiment revealed that the d(G[8- N 3]T) lesions could strongly block the A-family BF polymerase from Bacillus stearothermophilus , Y-family polymerases Dpo4 from Sulfolobus sulfataricus P2 and human Pol κ , with bypass efficiencies being <1–2%, ∼8%, and 9–11%, respectively. 261 In addition, the primer extension catalyzed by Pol η was also partially inhibited (with bypass efficiency being 28–45%) by the d(G[8- N 3]T) cross-links, and more efficient bypass of nonadjacent d(G[8- N 3]T) lesions in the GCT sequence context was observed than the adjacent counterpart in the GT sequence context.…”
Section: Repair and Biological Consequences Of Oxidative Stress-inmentioning
confidence: 99%
“…In contrast to 5′,8-cyclopurine lesions, the G*CT* and G*T* IntraCL lesions are incised in human HeLa cell extracts by BER as well as by NER mechanisms [101]. Detailed studies with purified repair proteins have shown that the bacterial, yeast, and human bifunctional DNA glycosylases (Nei, NEIL1, Nth, NTH1), as well as AP endonucleases (Nfo, Apn1 and APE1) cleave the strands adjacent to the G*CT* and G*T* IntraCL lesions (Fig.…”
Section: Interplay Between Ber and Ner Pathways In The Repair Of Omentioning
confidence: 99%
“…3), in combination with MALDI-TOF/MS methods, showed that the DNA glycosylases/AP lyases excise the cross-linked guanine and cleave the resulting abasic sites via β- and β,δ-elimination mechanisms. In turn, the AP endonucleases of E. coli, Nfo, yeast Apn1 and human APE1 cleave the duplex DNA containing G*CT* and G*T* lesions on the 5′-side of the cross-linked guanine, and are thus capable of initiating the nucleotide incision repair pathway [101]. These experiments were performed with purified proteins in vitro and clearly show that the G*T* and G*CT* intrastrand crosslinks are efficiently incised by BER and NIR pathways at the sites of these lesions.…”
Section: Interplay Between Ber and Ner Pathways In The Repair Of Omentioning
confidence: 99%